Synthesis, crystal structure, DFT calculation and catalytic activity of a polymer complex of zinc(II) succinate with 2-amino-1,3,4-thiadiazole - Nuralieva, Guzal; Alieva, Mushtariy; Torambetov, Batirbay; Leslee, Denzil Britto Christopher; Senthilkumar, Beeran; Kaur, Simranjeet; Dabke, Niteen B.; Vanka, Kumar; Ashurov, Jamshid; Kadirova, Shakhnoza; Gonnade, Rajesh G. (Journal of Molecular Structure, 2025)
A polymer complex of zinc(II) succinate with a 2-amino-1,3,4-thiadialole ligand, denoted as [Zn2L2(suc)2]n, was synthesized and characterized by NMR, ESI-MS, FTIR, and FT-Raman spectroscopy, TGA, and X-ray crystallography. The polymer complex crystallizes in the orthorhombic noncentrosymmetric Pna21 space group and features a five-coordinate zinc ion in a distorted spherical square pyramidal geometry. The Hirshfeld surface analysis was carried out to evaluate the intermolecular interactions. Additionally, computational studies were also conducted to assess the stability of the Zn polymer complex and analyze the electron density distribution of the HOMO and LUMO. The catalytic activity of our complex was tested, interestingly, that showed good results for Biginelli reactions with distinct substrate scope in good to high yield at mild reaction conditions.
Keywords: DFT; Dihydropyrimidinones; Polymer complex; succinate; Thiadiazole; zinc

Synthesis, crystal structure, Hirshfeld surface analysis and DFT calculations of the coordination compound tetraaquabis2-[(5-methyl-1,3,4-thiadiazol-2-yl)sulfanyl]acetato-κOcobalt(II) - Kinshakova, Ekaterina; Torambetov, Batirbay; Kaur, Simranjeet; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E Crystallographic Communications, 2025)
A relatively strong hydrogen bond between one of the water molecules and the non-coordinating carboxylate O atom consolidates the conformation. In the crystal, intermolecular hydrogen bonds lead to the formation of a complex tri-periodic structure. Hirshfeld surface analysis revealed that 30.1% of the intermolecular interactions are from H⋯H contacts and 20.8% are from N⋯H/H⋯N contacts. DFT calculations were performed to assess the stability and chemical reactivity of the compound by determining the energy differences between the HOMO and LUMO.